Development of Online-Based Cadre Infrastructure for Pimpinan Wilayah Nasyiatul Aisyiah of West Java - Akhmad Bakhrun; Iwan Awaludin; M. Rizqi Sholahuddin; Sofy Fitriani; Maisevli Harika; Setiadi Rachmat (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Nasyiatul Aisyiyah is part of the Persyarikatan Muhammadiyah which is engaged in da'wah among the younger generation aged 18-40 years. This generation is a productive generation who are usually pursuing a career or family. The leadership of the Nasyiatul Aisyiyah Region (Pimpinan Wilayah Nasyiatul Aisyiah, PWNA) during this pandemic has a regeneration problem. The main reason is that there are no online regeneration facilities. In addition, PWNA has not received knowledge about online learning systems, such as how to know the level of interest of a cadre when participating in online training, attracting cadres to continue to be interested in participating in training, and so on. This causes the regeneration process of cadres in an organization to be hampered. On the other hand, the lack of motivation to complete the course after registering causes the course completion rate to be low. A possible solution to overcome this problem is to do online regeneration with MOOC. The MOOCs system is a distance learning model. The MOOC system for this regeneration will use gamification. Gamification is the application of learning to follow elements such as in a game or game. By imitating like a game, it is hoped that it can motivate cadres in the learning process. So that the regeneration system can increase the interest of cadres to the learning. The output target of this Community Service (PkM) is the availability of Moodle-based MOOCs with gamification features in West Java PWNA. In addition, partners are expected to be able to operate the system independently, such as preparing content on the system. In addition, the system is also able to regulate access to materials according to the level of cadre members. Access rights to a material will be controlled automatically and the instructor can form statistics on participant reports systematically.